Soy canción que se fue/ de jonrón” (I am a Song that Became a Home Run). Translation, Performance and Archive in the Videopoems of Legna Rodríguez Iglesias - Garbatzky, Irina (Universidad Pedagógica y Tecnológica de Colombia, 2023)
In accordance with several contemporary trends (Laddaga 2009, Bourriaud 2009, Groys 2014), Legna Rodríguez Iglesias's writing can be read as a continuous performance between different literary and artistic genres, intermediary and audiovisual supports. However, its traslaticia condition builds an original poetics insofar as it reuses anachronistic forms of the Latin American archive and repertoire (Taylor, 2015), -fundamentally those that are based on a narrating voice-, to build a feminine and migrant writing. In his videopoems we observe the recovery of a rhymed poetry, of oral tradition; as well as certain themes and formats that recover and disarm classic motifs of Cuban literature in which the figure of José Martí resonates: the tones of a literature for the children of America and the portable roots of a poet in the big city.